3D Printing Architecting Reservoir‐Integrated Anode for Dendrite‐Free, Safe, and Durable Zn Batteries. Issue 12 (1st February 2022) - Zeng, Li; He, Hanna; Chen, Haiyan; Luo, Dan; He, Jun; Zhang, Chuhong
Abstract: The growing demand for safe and renewable energy storage systems has driven the recent renaissance of Zn‐ion batteries (ZIBs). Nevertheless, the intrinsic drawbacks of inhomogeneous electric distribution and sluggish ion replenishment worsen the Zn dendrite issues that seriously impede their practical application. Herein, for the first time, a functional 3D printed reservoir‐integrated N‐doped carbon host (3DP‐NC) is designed to remodel the electric/ionic fields. The customized 3D printed structure equipped with regular micron‐sized holes induces reduced local current density and homogeneous electric distribution. The micron‐sized holes function as reservoirs to ensure unobstructed ion diffusion and quasi‐steady‐state ionic supplements. A N‐doping interfacial modification strategy is further employed to encourage a highly zincophilic surface, hence reducing the nucleation energy barrier and motivating uniform Zn nucleation. As a result, the Zn‐deposited 3DP‐NC electrode (3DP‐NC@Zn) affords dendrite‐free morphology and highly reversible Zn plating/stripping with an ultra‐small overpotential of 15.3 mV even at 10 mA cm −2 . Additionally, these appealing features also endow the 3DP‐NC@Zn electrode with an outstanding lifespan over 380 h at 1 mA cm −2 and 1 mAh cm −2 . The thrilling performance establishes a new roadmap that advances the development of dendrite‐free and durable metal batteries by exploiting this unique 3D printing technique. Abstract : A 3D‐printing strategy is applied to construct a reservoir‐integrated N‐doped carbon host (3DP‐NC) with remodeled electric/ionic fields. Benefiting from the reduced local current density, homogeneous electric distribution, unobstructed ion diffusion and quasi‐steady‐state ionic supplements, the 3DP‐NC@Zn electrode features highly reversible Zn plating/stripping with ultra‐small overpotential at high current density as well as excellent cycling life span.